Association Between Attempted Arteriovenous Fistula Creation and Mortality in People Starting Hemodialysis via a Catheter: A Multicenter, Retrospective Cohort Study. (July 2021) - Roberts, Derek J.; Clarke, Alix; Elliott, Meghan; King-Shier, Kathryn; Hiremath, Swapnil; Oliver, Matthew; Quinn, Robert R.; Ravani, Pietro
Background: In North America, most people start hemodialysis via a central venous catheter ("catheter"). These patients are counseled to undergo arteriovenous fistula ("fistula") creation within weeks of starting hemodialysis because fistulas are associated with improved survival. Objectives: To determine whether attempting to create a fistula in patients who start hemodialysis via a catheter is associated with improved mortality. We also sought to determine whether differences in baseline patient characteristics, vascular procedures for access-related complications, or days in hospital may confound or mediate the relationship between attempted fistula creation and mortality. Design: Multicenter, retrospective cohort study. Setting: Six dialysis programs located in Ontario, Alberta, and Manitoba. Patients: Patients aged ≥18 years who initiated hemodialysis via a catheter between January 1, 2004, and May 31, 2012, who had not had a previous attempt at fistula creation. We excluded those who had a life expectancy less than 1 year, who transitioned to peritoneal dialysis within 6 months of starting dialysis, and people who started hemodialysis via a graft. Measurements: Attempted fistula creation, all-cause mortality, patient characteristics and comorbidities, vascular procedures for access-related complications, and days spent in hospital. Methods: We used survival methods, including marginal structural models, to account for immortal time bias and time-varying confounding. Results: In total, 1832 patients initiated hemodialysis via a catheter during the study period and met inclusion criteria. Of these patients, 565 (31%) underwent an attempt at fistula creation following hemodialysis start. As compared to those who did not receive a fistula attempt, these people were younger, had fewer comorbidities, and were more likely to have started dialysis as an outpatient and to have received pre-dialysis care. In a marginal structural model controlling for baseline characteristics and comorbidities, attempted fistula creation was associated with a significantly lower mortality (hazard ratio [HR] = 0.53; 95% confidence interval [CI] = 0.43-0.66). This effect did not appear to be confounded or mediated by differences in the number of days spent in hospital or vascular procedures for access-related complications. It also remained similar in analyses restricted to patients who survived at least 6 months (HR = 0.60; 95% CI = 0.47-0.77) and to patients who started hemodialysis as an outpatient (HR = 0.48; 95% CI = 0.33-0.68). Limitations: There is likely residual confounding and treatment selection bias. Conclusions: In this multicenter cohort study, attempting fistula creation in people who started hemodialysis via a catheter was associated with significantly reduced mortality. This reduction in mortality could not be explained by differences in patient characteristics or comorbidities, days spent in hospital, or vascular procedures for access-related complications. Residual confounding or selection bias may explain the observed benefits of fistulas for hemodialysis access. Trial Registration: Not applicable (cohort study).